Selecting a complete sample of blazars in sub-millimetre catalogues. Issue 4 (17th May 2022) - Massardi, M; Bonato, M; López-Caniego, M; Galluzzi, V; De Zotti, G; Bonavera, L; González-Nuevo, J; Lapi, A; Liuzzo, E
ABSTRACT: The Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS), which has covered about 642 sq. deg. in five bands from 100 to 500 μ m, allows a blind flux-limited selection of blazars at sub-mm wavelengths. However, blazars constitute a tiny fraction of H-ATLAS sources and therefore identifying them is not a trivial task. Using the data on known blazars detected by the H-ATLAS, we have defined a locus for 500 μ m selected blazars and exploited it to select blazar candidates in the H-ATLAS fields. Candidates and known blazars in the H-ATLAS equatorial and South Galactic Pole fields were followed up with the Australia Telescope Compact Array (ATCA) or with the Karl G. Jansky Very Large Array (VLA), and matched with existing radio- and mm-catalogues to reconstruct the spectral behaviour over at least six orders of magnitude in frequency. We identified a selection approach that, combining the information in the sub-mm and radio domains, efficiently singles out genuine blazars. In this way, we identified a sample of 39 blazars brighter than S_500μ m = 35 mJy in the H-ATLAS fields. Tests made cross-matching the H-ATLAS catalogues with large catalogues of blazar candidates indicate that the sample is complete. The derived counts are compared with model predictions finding good consistency with the C2Ex model and with estimates based on ALMA data.